La part du langage : pratiques professionnelles en formation - Sébastien Chaliès (Communiquer)
The present review discusses the book La part du langage : pratiques professionnelles en formation co-edited by K. Balslev, L. Filliettaz, S. Ciavaldini-Cartaut et I. Vinatier. In terms of structure, this book is composed of nine chapters, divided into two parts, respectively titled (we translate) “The language part in the tutorial activity” and “Language mediations and professional development in teacher education”. In terms of content, this book examines two main objects related, for one, to the effects of interactions during a tutorial vocational training situation and, for the other, to the complexity of the interactions between the person(s) trained and the trainer(s) in this type of situation.